Exploring Cyberbullying among High School Students in Surakarta - Haq, Aniq Hudiyah Bil; Raihana, Permata Ashfi; Purwandari, Eny (Universitas Muhammadiyah Surakarta, 2016)
Advances in technology have both positive and negative impacts., When an individual acts and it injures another person using information technology media, then it can be considered as an activity of cyberbullying. However, the problems caused by cyberbullying cannot be ignored, especially cyberbullying among the high school students. This study explored the intensity of cyberbullying and other factors (gender, cyberperpetrator, bystanders, forms of cyberbullying and the victims) among high school students in Surakarta. The survey method was performed on 290 students at junior high school and 200 students at senior high school in Surakarta . Data collectionwas assessed by the scale of cyberbullying. The results of this study showed that 308 subjects or around 62.9% had never done cyberbullying activity and 37.1% subject had ever done cyberbullying activity. The respondents did cyberbullying for amusement, it means that one among the intentions of cyberbullying was to make fun someting or someone, because they had many time using the internet access (33.9% had more than 3 hours/day). The forms of cyberbullying in high school students was by sending or posting gossip or rumors to damage a reputation of someone or something.